Food insecurity as a basis for drafting a Strategic Food Sovereignty Plan: A case study of the Kutai Kartanegara District, Indonesia - Subejo, .; Fidiashtry, Al; Aryudiawan, Candra; ., Suadi; L, Awaluddin; Marfai, Muh Aris (Quaestiones Geographicae, 2017)
This study aims to analyse food sovereignty strategies in an effort to eradicate poverty in a micro-scale region by strengthening its food security status. The research was conducted in the Kutai Kartanegara District East Kalimantan Province in Indonesia. Food insecurity status in the study area was determined based on nine food security indicators. The 237 villages in the Kutai Kartanegara District were ranked based on four classifications of vulnerability to food insecurity. The results showed that 3.80% of the villages were highly vulnerable, 5.06% were vulnerable, 8.86% were slightly vulnerable and 82.28% were food secure. While Kutai Kartanegara was a food secure district, in order to maintain its food security status and enhance the performance of the villages that are still vulnerable to food insecurity, local government, and related stakeholders must work together to develop strategies to improve agricultural productivity, increase the region’s human resources capability and strengthen its infrastructure so food can be more readily accessed.